2017
DOI: 10.1261/rna.063453.117
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants of the folding properties of box C/D kink-turns in RNA

Abstract: Folding properties differ markedly between kink-turns (k-turns) that have different biological functions. While ribosomal and riboswitch k-turns generally fold into their kinked conformation on addition of metal ions, box C/D snoRNP k-turns remain completely unfolded under these conditions, although they fold on addition of L7Ae protein. Sequence elements have been systematically exchanged between a standard ribosomal k-turn (Kt-7) that folds on addition of metal ions, and a box C/D kturn. Folding was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Some, but importantly not all, k-turns become stabilized on addition of metal ions (Goody et al 2004;Liu and Lilley 2007). Whether or not a given k-turn folds in response to metal ions depends upon its sequence, and we have found that two sequence elements act as key determinants of this behavior (McPhee et al 2014;Ashraf et al 2017). Protein binding provides an alternative way to stabilize the folded k-turn.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Some, but importantly not all, k-turns become stabilized on addition of metal ions (Goody et al 2004;Liu and Lilley 2007). Whether or not a given k-turn folds in response to metal ions depends upon its sequence, and we have found that two sequence elements act as key determinants of this behavior (McPhee et al 2014;Ashraf et al 2017). Protein binding provides an alternative way to stabilize the folded k-turn.…”
Section: Introductionmentioning
confidence: 78%
“…the absence of protein binding. We have previously studied this in some depth (McPhee et al 2014;Ashraf et al 2017), and have identified two critical sequence elements that determine the ability of a k-turn to fold in response to the presence of metal ions.…”
Section: The Predicted Folding Ability Of K-turns In L7ae Gene Utrsmentioning
confidence: 99%
See 3 more Smart Citations